Analytical solutions for rollover instability of concrete beams on elastomeric bearing pads. (1st November 2018) - Krahl, Pablo Augusto; Carrazedo, Ricardo; El Debs, Mounir Khalil
Highlights: New analytical solutions for rollover load of precast beams on bearing pads are presented. The proposed equations predict very well the experimental results published in the literature. Tolerances for initial imperfections are proposed based on Monte Carlo simulations. Abstract: During construction, concrete beams are susceptible to rollover failure when unbraced and supported by elastomeric bearing pads. This failure occurs mainly due to the presence of initial horizontal curvature of the beam and the low torsional restraint provided by the supports. Besides, the uncertainties and variability about modulus of elasticity, initial imperfections and supports conditions can increase the risk of collapse of such elements. In contrast, there is a lack in analytical equations to predict the few published experimental results in this field that present different loading conditions from self-weight. Also, another lack is about recommendations of required pad stiffness for beam stability during construction. Thus, the current research focuses on presenting closed-form analytical solutions to predict the rollover load of beams supported by bearing pads and subjected to different loading conditions. Furthermore, this paper presents recommendations about required pad stiffness for the standard AASHTO bulb-tee beams subjected to self-weight. The variational Rayleigh-Ritz method enabled to determine the analytical solutions, and furthermore, the classical Southwell equation allowed to consider the effect of initial sweep on the beam stability. With this, the required pad stiffness was determined through Monte Carlo simulations. The proposed equations accurately predicted the experimental results available in the literature. The analytical and experimental rollover loads differed by 4.37% and 13.6% for the two studied cases. Besides, Monte Carlo simulations were performed to determine tolerances for initial imperfections.